The role of Pharmacogenomics in the Personalization of Parkinson’s Disease Treatment in Egyptian Regions - William, Martina (AUC Knowledge Fountain, 2025)
Introduction: Parkinson's disease (PD) is an age-related neurodegenerative disorder that is characterized by both motor and non-motor manifestations. Its etiology remains elusive, and current treatments are only symptomatic. Genetic predispositions to Parkinson's disease (PD) vary significantly across populations. PD has not been extensively studied genetically in Egypt, revealing a gap in understanding the genetic underpinnings of the disease in this region. Objective: Our objective is to conduct the largest genetic study of Parkinson's Disease (PD) in Egypt. This study will also be the first to include pharmacogenomic screening of FDA-approved drugs and natural products to identify potential therapeutic targets, focusing on Egyptian-specific mutated variants. This approach is extremely important for countries with limited resources, as it is more advantageous in terms of cost and time-saving compared to identifying novel targets. Methods: We examined 1,210 Egyptians (611 PD patients and 599 controls) from 16 governorates for 12 LRRK2 pathogenic variants, and 479 PD patients and 481 controls for two APOE and one MAPT pathogenic variant, along with other rare variants. Additionally, we conducted structure-based virtual screening of DrugBank, NANPDB, and EANPDB databases based on the discovery of the G2019S mutation in the Egyptian population using the cryo-electron microscopy (cryo-EM) structure of the C- terminal domain of leucine-rich repeat kinase 2 (LRRK2) with the G2019S mutation. Results: The p.Gly2019Ser variant was the only detected variant, with a prevalence of 4.1% in sporadic cases, 6.5% in familial cases, and 0.68% in controls. All p.Gly2019Ser carriers, except one homozygous patient, were heterozygous, sharing the common haplotype 1. Demographics and UPDRS scores did not differ between carriers and non-carriers, with most patients being males who developed PD in their fifties. Young and Early-onset PD prevalence was 37.5% in carriers and 33% in non-carriers. While there was no association between APOE and PD risk, there was a notable correlation with age of onset, particularly in males. MAPT showed no significant link to disease presence or age at onset. No meaningful associations were detected between PD and the BCHE and KANSL1 genes. Our in-silico virtual screening identified top candidates: Estrone, Fluoroestradiol F-18, and Adapalene from DrugBank; Lettowianthine and other compounds from EANPDB; and Dehydrobenzophenanthridine and others from NANPDB. Conclusion: This study confirms that Egyptians with PD have a higher prevalence of the p.Gly2019Ser variant, similar to other Mediterranean populations. LRRK2 inhibitors could be promising therapeutic options for this population. Our virtual screening findings highlight the potential for repurposing existing compounds and suggest new therapeutic development avenues targeting the G2019S mutation in LRRK2 in Egypt. Keywords: Parkinson’s Disease, LRRK2, APOE, MAPT, Structure-based virtual screening, G2019